Upper Airway Stimulation for Obstructive Sleep Apnea: Past, Present, and Future - Dedhia, Raj C.; Strollo, Patrick J.; Soose, Ryan J. (Sleep (New York, N.Y.), 2015)
Obstructive sleep apnea (OSA) is an increasingly prevalent clinical problem with significant effects on both personal and public health. Continuous positive airway pressure (CPAP) has demonstrated excellent efficacy and low morbidity; long-term adherence rates approach 50%. Although traditional upper airway surgical procedures target the anatomic component of obstruction, upper airway stimulation tackles the twin goals of improving anatomic and neuromuscular pathology. After decades of trials demonstrating proof of concept of hypoglossal nerve stimulation in animal and human subjects, the results of a large multicenter, prospective trial were recently published. The trial demonstrated that hypoglossal nerve stimulation led to significant improvements in objective and subjective measurements of the severity of OSA. This novel approach is the first to combine sleep surgery techniques with a titratable medical device for the treatment of OSA. Further research is required to define optimal patient selection and device performance and to demonstrate long-term effectiveness.